Cracking Characteristics of Different Crack Forms in Pavement under Moving Load - YAN, Guannan (Engineering Transactions, 2024)
In road engineering, the crack damage problems are one of the essential research areas that need to be emphasized. However, there have been few researches on the effects caused by different crack forms, e.g., the impacts of the distribution and propagation directions of formed cracks on subsequent cracking characteristics. In this study, two road models, including double cracks with different distribution and propagation directions, were established in ABAQUS software, and the potential cracking characteristics of such crack forms under moving load were investigated through numerical analysis. The simulation results demonstrated that the distribution and propagation directions of cracks are critical in affecting potential cracking modes and stress intensity factors. In more detail, a deeper crack tip with respect to the road surface tends to bring about the cracking with the first mode within a certain depth range. Additionally, a larger angle between the distribution direction of cracks and the traffic direction can promote the cracking with the second mode. Due to the too low numerical level of the stress intensity factor under the third mode at the middle crack tip, cracking with the third mode is generally unlikely for the middle zone of cracks in the pavement under a moving load. In view of this, on the premise that all cracks have the same sizes, a reflective crack is more likely to extend with the first mode than a top-down crack within a certain depth range, and compared with a longitudinal crack, a transverse crack has a higher potential to propagate with the second mode. Therefore, transverse reflective crack is a severe form of damage that needs to be detected as early as possible and repaired promptly.